An ideal e‐health system for pelvic floor muscle training adherence: Systematic review. Issue 1 (30th October 2018) - Latorre, Gustavo F. S.; de Fraga, Rogério; Seleme, Maura R.; Mueller, Cláudia V.; Berghmans, Bary
Abstract : Background: Nowadays, Pelvic Floor Muscle Training (PFMT) is a first line, level 1 evidence‐based treatment for urinary incontinence (UI), but adherence to PFMT is often problematic. Today, there are several mobile applications (mApps) for PFMT, but many lack specific strategies for enhancing adherence. Aims: To review available mApps for improvement of adherence to PFMT, and to introduce a new App so called iPelvis. Methods: Review study all available mApps for PFMT and relevant literature regarding adherence by electronic search through the databases Pubmed, Embase, CINAHL, LILACS, PEDro, and Scielo. Based on these results, development of a mApp, called "iPelvis" for Apple™ and Android™ systems, implementing relevant strategies to improve adherence. Results: Based on the current adherence literature we were able to identify 12 variables helping to create the optimal mApp for PFMT. None of the identified 61 mApps found for Android™ and 16 for Apple™ has all these 12 variables. iPelvis mApp and websites were constructed taking into consideration those 12 variables and its construct is now being subject to ongoing validation studies. Conclusion: MApps for PFMT are an essential part of first‐line, efficient interventions of UI and have potentials to improve adherence, in case these respect the principles of PFMT, motor learning and adherence to PFMT. iPelvis has been constructed respecting all essential variables related to adherence to PFMT and may enhance the effects of UI treatment.